Major Life Events Are Associated with Depression among Employees of a Public University - Yahya, Fariza; Othman, Zahiruddin; Fadzil, Nor Asyikin (Japan International Cultural Exchange Foundation, 2019)
Introduction: University employees are increasingly pressured to perform, which potentially lead to increased job stress. Stressful life events increase the risk of developing depression and lead to reduced productivity. Objectives: This study aims to determine the prevalence of depression and its predictors among the employees of a public university. Methods: In this cross-sectional study over a period of 4 months, validated Malay version of the Hospital Anxiety and Depression scale, Job Stress Scale and Social Readjustment Rating Scale were utilized for measurement of depression, job stress, and stressful life events, respectively. Results: A total of 300 employees of a public university attending the staff clinic were recruited. The prevalence of depression was 12.7%. Using multiple logistic regression analyses, the presence of major life events had an adjusted odds ratio of 2.30 with depression. Other socio-demographic and job-related factors were non-significant. Conclusion: Presence of major life events in the preceding year is independently associated with depression among the employees of a public university. Future study needs to explore the nature and individual's perception of specific stressful life events